2020
DOI: 10.1002/hbm.25289
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in the blind brain: A coordinate‐based meta‐analysis

Abstract: Social cognition skills are typically acquired on the basis of visual information (e.g., the observation of gaze, facial expressions, gestures). In light of this, a critical issue is whether and how the lack of visual experience affects neurocognitive mechanisms underlying social skills. This issue has been largely neglected in the literature on blindness, despite difficulties in social interactions may be particular salient in the life of blind individuals (especially children). Here we provide a meta‐analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 117 publications
(188 reference statements)
1
13
0
Order By: Relevance
“…The present study adds to a growing body of research suggesting that the brain of EB and SC are similarly organized at the functional level (Proulx et al, 2014;Cecchetti et al, 2016;Arioli et al, 2021). Particularly, our ALE analysis supports the amodal spatial processing hypothesis (Loomis et al, 2012;Chebat et al, 2018a;Giudice, 2018) as it indicates that EB and SC share common neural networks mediating spatial processing of sensory information, spatial navigation, and the formation of spatial representations.…”
Section: Amodal Nature Of Spatial Cognition and Navigationsupporting
confidence: 79%
“…The present study adds to a growing body of research suggesting that the brain of EB and SC are similarly organized at the functional level (Proulx et al, 2014;Cecchetti et al, 2016;Arioli et al, 2021). Particularly, our ALE analysis supports the amodal spatial processing hypothesis (Loomis et al, 2012;Chebat et al, 2018a;Giudice, 2018) as it indicates that EB and SC share common neural networks mediating spatial processing of sensory information, spatial navigation, and the formation of spatial representations.…”
Section: Amodal Nature Of Spatial Cognition and Navigationsupporting
confidence: 79%
“…We performed six distinct ALE analyses, using the GingerALE 3.0.2 software (Eickhoff et al, 2009), to identify regions consistently associated with: (1) mentalizing, (2) affective mentalizing, (3) cognitive mentalizing, (4) empathic processing, (5, 6) mentalizing and empathic processing in HCs compared with SC patients, (7, 8) mentalizing and empathic processing in autistic patients compared with HCs. We followed the analytic approach previously described by Arioli, Gianelli, et al (2020), Arioli, Ricciardi, et al (2020) and Arioli and Canessa (2019), based on Eickhoff et al (2012). Importantly, the inclusion of multiple contrasts/experiments from the same set of subjects can generate dependence across experiment maps and thus decrease the validity of meta‐analytic results.…”
Section: Methodsmentioning
confidence: 99%
“…We used the GingerALE software 3.0.2 ( Eickhoff et al, 2009 ) to conduct a set of ALE analyses aiming at the identification of the brain areas associated with social perception in either PD patients, HC, or both groups. We followed the method described by Eickhoff et al (2012) , resulting in the same procedure reported in Arioli et al (2021) . In a first step, each of the activation coordinates derived from the selected studies, keeping separate those related to PD patients from the HC ones, was taken as the centre of a three-dimensional Gaussian probability distribution capturing the spatial uncertainty intrinsically associated with the coordinate data.…”
Section: Methodsmentioning
confidence: 99%